Assessing Outcomes and Effectiveness of Character Education Model Based on Classroom Guidance Services in Junior High Schools - Barus, Gendon (COUNS-EDU: The International Journal of Counseling and Education, 2017)
The aim of this study is to measure the gain and effectiveness of the character education model based  on classroom guidance service in several junior high schools in Indonesia. This research was designed by adopting the research and development model (Borg & Gall, 1983). The research stage began with preliminary research to construct conceptual maps for hypothetical model design that developed, supporting instrument design, and initial draft of Character Education Module for junior high school Volume 1, 2 and 3. Development episode focus on the concreteness of all model tools in the form of instruments, preparation of modules and media implementation of character education in junior high school and followed by scientific procedures — test, validation, revision, limited simulation of model usage. Limited product implementation trials were conducted on nine junior high schools nationwide across Indonesia. Implementation testing (limited) models showed encouraging results. From the analysis of the implementation of this model, there is an increase in character education outcomes between pre-and posttest on those nine junior high school, and both teachers and students in the 9 schools assessed that this model is much more effective than the integrated character education model.